2021
DOI: 10.1108/ijhma-08-2020-0100
|View full text |Cite
|
Sign up to set email alerts
|

Hedonic housing prices and environmental quality in Lebanon

Abstract: Purpose This study aims to examine the impact of local air pollution on housing prices in Lebanon. Design/methodology/approach The authors apply a hedonic pricing approach using a unique data set from Lebanon. To account for non-linearities in pricing, the authors use three different functional regression forms for the hedonic model approach. The authors also deal with potential omitted variable bias by estimating a hedonic frontier specification. Findings The authors find that, in all specifications, air … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Moreover, the distance to the Jieh and Zouk power plants is measured in kilometers. Lastly, the distance between the dwelling and the Costa-Brava, Hammoud and Naameh landfills is also measured (Marrouch and Sayour, 2021) [2].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, the distance to the Jieh and Zouk power plants is measured in kilometers. Lastly, the distance between the dwelling and the Costa-Brava, Hammoud and Naameh landfills is also measured (Marrouch and Sayour, 2021) [2].…”
Section: Methodsmentioning
confidence: 99%
“…We use a recent cross-sectional data set collected from Lebanon. This unique data set is collected by Marrouch and Sayour (2021) and it includes local air pollution concentrations, dwellings characteristics and their prices, in addition to information about the location of the dwelling. The dwellings' characteristics are retrieved from "Property Finder Lebanon" in 2018.…”
Section: Datamentioning
confidence: 99%
See 2 more Smart Citations
“…This finding is supported by those from a study on two coastal cities in Alabama, United States, in which a 1% increase in the distance to water bodies was found to decrease house prices by 0.03-0.04% (Dahal et al, 2019[66]). Furthermore, a 1% increase in proximity to wetlands was found to increase house prices by 0.04% in Portland Oregon (Mahan, Polasky and Adams, 2000 [67]). However, several papers found that proximity to water bodies, such as rivers and streams, had no clear effect on house prices (Cohen, Cromley and Banach, 2015 [68]; Van Der Kruk, 2001 [69]; Mei, Sohngen and Babb, 2018 [70]; Sylla, Lasota and Szewrański, 2019 [71])…”
Section: Water Bodiesmentioning
confidence: 99%